MULTIPLICATION AND ACCLIMATIZATION OF BANANA VARIANT CV. AMPYANG (Musa acuminata, AAA) PUTATIVE RESISTANCE TO FUSARIUM WILT - Indrayanti, Reni; Yanti, Fitri; Adisyahputra, Adisyahputra; Dinarti, D; Sudarsono, Sudarsono (LPPM Universitas Negeri Jakarta, 2018)
Abstract Plants resistance to Fusarium wilt can be developed by mutation breeding and in vitro selection techniques. The objectives of this research were to evaluated growth and development of banana plantlets cv. Ampyang (Musa acuminata, AAA) resistance to Fusarium wilt. The plant material used in this study was 9 (nine) code clones banana cv. Ampyang result from mutations induced by gamma irradiation (30, 45, and 50 Gy) and in vitro - in vivo selection, a collection of Plant Tissue Culture Laboratory Department of Biology UNJ. Plantlets multiplied for four months on Murashige and Skoog supplemented with2.25 mgL-1 Benzyl amino purine and 0.22 mgL-1 Thydiazuron and 0.175 mgL-1 Indole 3 acetyc-acid . Acclimatization and evaluation of plantlet growth and development in a greenhouse showed that percentage of survival rate of plantlet were ranging from 42.9 – 100%. There was phenotypic variation among those plantlet investigated in quantitative and qualitative character. Plantlet regenerated from clone A regenerated from gamma irradiation 30 Gy and after in vitro selection of Foc from isolate Medan showed significantly the highest number of leave and fresh weight. The less number of roots length and other phenotypic character were produced from clone B, D and F. All of the regenerated plantlets were successfully transferred into soil and they would be used to evaluate the existence of variants in a greenhouse. Keywords: phenotypic variation, induce mutation and in vitro selection, shoot multiplication, Foc isolates from Medan